Kadar Perasan Kunyit yang Efektif Memperbaiki Kerusakan Hati Mencit yang Dipicu Karbon Tetrachlorida (THE EFFICACY OF TURMERIC JUICE ON PATHOLOGICAL CHANGES OF THE MICE LIVER BY INDUCED CARBON TETRACHLORIDE) - Kardena, I Made; Winaya, Ida Bagus Oka (Jurnal Veteriner; Vol 12 No 1 (2011), 2012)
A study on effect of various concentrations of turmeric juice on pathological changes mice liver hasbeen carried out. As many as 25 mice were used in this study and they were divided into 5 groups, i.e.: groupK-: 0.2 ml vegetable oil without CCl4; group K+: CCl4 without turmeric extract; group T1: CCl4 with 10%turmeric extract; group T2: CCl4 with 20% turmeric extract and group T3: CCl4 with 30% turmeric extract.All mice, except the K- group, were treated with 0.2 ml CCl4 orally for 7 days. On day-8 to day-29, the CCl4treated mice were given various concentrations of turmeric extract, i.e.: 10%, 20% and 30%; whereas, the KandK+ groups were given drinking water adlibitum. On day-30, all mice were sacrificed and their livertissues were collected and then processed to histopathological staining with haematoxylin-eosin. Theresult showed a clear evidence to suggest that turmeric extract can induce a better recovery compared tonon-treated mice. The improvement of pathological condition was characterized by reduction of pathologicalchanges found in the liver cells of mice, such as: hidrophic degeneration. fatty degeneration, and necrosis.More importantly, treatment with 30% of turmeric juice induced a better recovery than those with 10%and 20%.
Keywords: Turmeric juice, Mice, Liver degeneration